CLINICAL AND EPIDEMIOLOGICAL CORRELATION OF HEPATITIS B IMMUNIZATION IN BRAZIL - Pereira, Ana Paula Macedo; Dà©roulà¨de, Letàcia Faria; Camapum, Luàza De Miranda; dos Santos , Maria Eduarda Ivo; Silva, Milena Lima; Fagundes, Sibelle Moreira; Labre, Luciana Vieira Queiroz (CIPEEX, 2022)
HEPATITIS B IS CONSIDERED A WORLDWIDE PUBLIC HEALTH PROBLEM, ESPECIALLY IN DEVELOPING COUNTRIES LIKE BRAZIL. THIS STUDY AIMED TO EVALUATE THE HEPATITIS B IMMUNIZATION IN BRAZIL ASSOCIATED WITH ITS EPIDEMIOLOGY, PATHOPHYSIOLOGY AND CLINICAL ASPECTS. A BIBLIOGRAPHIC SURVEY WAS CARRIED OUT IN MEDLINE, LILACS, PUBMED, SCIELO AND PORTAL DE PERIÓDICOS CAPES/MEC DATABASES. 20 REFERENCES WERE CHOSEN ACCORDING TO INCLUSION AND EXCLUSION CRITERION. FROM THESE STUDIES, IT WAS OBSERVED THAT HEPATITIS B CAN DEVELOP INTO ACUTE OR CHRONIC INFECTION, THE LATTER BEING DIVIDED INTO FOUR STAGES: IMMUNOTOLERANT, IMMUNOACTIVE, NON-REPLICATIVE AND REACTIVATION. IT HAS BEEN FOUND THAT HEPATITIS B PREVALENCE RATES HAVE BECOME LOWER ACROSS THE COUNTRY AS A RESULT OF NATIONAL CONTROL STRATEGIES. HOWEVER, THE AMAZON REGION WAS THE MOST ENDEMIC IN THE COUNTRY. KNOWLEDGE OF VACCINATION HISTORY AND SEROLOGICAL STATUS, ATTITUDES AND APPROPRIATE PRACTICES OF HEALTH PROFESSIONALS ARE ESSENTIAL FOR POST-EXPOSURE MANAGEMENT. THE EXISTENCE OF A LOW VACCINATION COVERAGE WAS DEMONSTRATED IN THE AMAZON AND IN THE NORTHEAST REGION AND A BROADER VACCINATION COVERAGE WAS VERIFIED IN THE SOUTHEAST REGION. VACCINATION IN ADOLESCENTS, HEALTH WORKERS, UNIVERSITY STUDENTS AND GARBAGE COLLECTORS WERE ANALYZED. IN THE CASE OF DIAGNOSIS, IMMUNOENZYMATIC ASSAYS AND CHEMILUMINESCENCE ARE USED. FINALLY, HEALTH CARE WORKERS WERE CONSIDERED A RISK GROUP FOR HEPATITIS B AND SHOULD BE PROPERLY IMMUNIZED. THEREFORE, IT WAS POSSIBLE TO CONCLUDE THAT THE RESULTS ARE VALID, AS THEY ALLOW INFORMATION WITH SCIENTIFIC RELEVANCE TO BE MADE AVAILABLE QUICKLY, SO THAT THERE IS GREATER AWARENESS ABOUT ASPECTS OF HEPATITIS B AND THE IMPORTANCE OF VACCINATION AGAINST THIS DISEASE. HOWEVER, THE NEED FOR MORE RESEARCH ON THE SITUATION OF HEPATITIS B IN BRAZIL IS CLEAR, IN ORDER TO UPDATE THE EPIDEMIOLOGICAL CONTEXT AND FOR NEW STRATEGIES TO BE DEVISED.